The Relationship between Social Capital and Organizational Learning in the Selected Hospitals of Zabol County - Marziye Yusefi; Masoud Arefnezhad; Ahmad Sadeghi; Alireza Yusefi (Kerman University of Medical Sciences, 2017)
Background & Objectives: Due to the importance of organizational learning and social capital in increasing efficiency and productivity in organizations, this study aimed to determine the relationship between social capital and organizational learning in two hospitals of Zabol County. Methods: This cross-sectional and descriptive-analytic study carried out on 290 staff of two hospitals in Zabol County. Data collection tools were Gomez organizational learning questionnaire and Nahapiet social capital questionnaire. Data were analyzed through SPSS23 and using t-test, ANOVA and Pearson correlation coefficient. Results: Mean age of subjects was 30.47±7.01years. Most of them were male (56%), had a bachelor's degree (60%), and were contractual personnel (47%). There was a significant positive relationship between social capital and organizational learning and between age and social capital (P=0.029). Also, organizational learning capacity showed significant relationship with age (P=0.017) and educational level (P=0.04). Conclusion: The status of social capital and organizational learning was estimated at a moderate level. In this context, by creating work teams, delegating more authority to employees, creating good work relationships among employees and job enrichment, the growth of social capital and the development of organizational learning in hospitals can be facilitated. Keywords: Social capital, Develop the learning capacity, Teaching Hospital Citation: Yusefi M, Arefnezhad M, Sadeghi A, Yusefi A. The Relationship between Social Capital and Organizational Learning in the Selected Hospitals of Zabol County. Journal of Health Based Research 2017; 3(1): 59-69.